COMPARATIVE ASSESSMENT OF MAGNESIUM SULFATE AND DEXMEDETOMIDINE AS ADJUNCTS TO 0.5% ROPIVACAINE IN SUPRACLAVICULAR BRACHIAL PLEXUS BLOCK - Mohamed Zaki Shaaban Youssef; Mai Medani Elsaid Medani; Muna Elamin Elfaki Elsheikh; Ehab Mohamed Ahmed Gharib Shalaby; Ahmed Agwa; Tarek Mohamed Refat Elhefni (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
AimThe aim is to assess and contrast the effectiveness of MgSO₄ and dexmedetomidine as ropivacaine adjuncts in supraclavicular brachial plexus blocks (SCBPB).Duration and place of Study: This study was conducted in Hatta Hospital Dubai Health, Dubai UAE from February 2022 to February 2024MethodologyIn this study three groups of fifty patients were randomly selected from 150 patients on the operation list for upper extremity orthopedic surgery. 29 mL of 0.5% ropivacaine plus 1 mL of normal saline was given to Group A; 29 mL of 0.5% ropivacaine plus 1 mL of dexmedetomidine (100 μg) was given to Group B; and 29 mL of 0.5% ropivacaine plus 1 mL MgSO₄ (150 mg) was given to Group C. The onset of the blocks and the duration of the blocks, the length of analgesia, the efficacy of the anesthetic, the total amount of analgesics consumed over a 24-hour period, the degree of drowsiness, and any problems were among the important metrics that were noted.ResultsGroup A exhibited the slowest start of sensory and motor blockages, whereas Group B showed the earliest onset, followed by Group C. Group A experienced the lowest block duration, Group B the longest, and Group C the middle. Group A experienced the lowest period of analgesia, whereas Group B experienced the longest, followed by Group C. Group B consumed the least amount of analgesics over a 24-hour period. Group B had the greatest ratings for anesthesia quality when compared to the other groups. Compared to Groups B and C, Group A had higher visual analog scale (VAS) scores. Group B's sedation scores were noticeably greater.ConclusionDexmedetomidine results in quicker onset of block, along with significantly extended durations of these blocks and analgesia, and reduced postoperative analgesic requirements compared to MgSO₄. However, dexmedetomidine use is associated with higher rates of hypotension, bradycardia, and sedation.